Sektor Industri Pengelompokan Dan Perusahaan Negara - Erwin Putra R D; Riska Putri D; Muhammad Yasin (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This research aims to analyze industrial sector groupings and the role of state companies in the economy. Using a qualitative approach, this study identifies various industrial sector categories and examines the contribution of state companies in each sector. Data was collected through in-depth interviews with industry experts and analysis of official documents from relevant government agencies. The research results show that the industrial sector grouping is based on product characteristics, technology used, and markets served. State companies play an important role in strategic sectors such as energy, infrastructure and transportation. In addition, this research found that the existence of state companies can help encourage economic growth, create jobs and increase the competitiveness of national industry. However, challenges faced include operational efficiency and the need for structural reforms to improve performance. This study provides recommendations for the government to strengthen regulations and policies that support the development of the industrial sector and state companies.